Pengaruh Model Problem-Based Learning terhadap Hasil Belajar Siswa pada Materi Gaya dan Gerak - Galang Pradana Kusuma; Damar Cahyo Wibowo (Jurnal Pendidikan Kimia, Fisika dan Biologi, 2025)
This study aims to analyze the effect of problem-based learning (PBL) models on student learning outcomes in the material of force and motion. This study used a quasi-experimental method with a pretest-posttest control group design. The research sample consisted of junior high school students who were divided into an experimental group with the PBL model and a control group with conventional learning. The results showed that students who learned with the PBL model had a deeper understanding of concepts and were able to apply concepts in solving everyday problems compared to the control group. The implications of this study confirm that the application of PBL can improve students' learning outcomes and critical thinking skills in physics learning.